(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Knowledge management (KM) is becoming a fad in an increasing way so many organizations are trying to apply it in order to enhance their organizational performance. In this paper, literatures were investigating critically in order to show the real influence of knowledge management and some of its practices on organizational performance. It founded that KM including knowledge process and infrastructure capabilities affect positively in a huge manner on all aspects of organizational performance directly or indirectly. In the same vein, there is a huge need to continuously train and educate the learning organizations’ CEOs about the importance of KM through group works and training programs. Knowledge management (KM) is becoming an important management responsibility as organizations increasingly invest significant information technology resources to support acquisition, storage, sharing, and retrieval of knowledge. Furthermore, KM plays a critical role in organizations that rely primarily on intellectual capital, such as software development companies. In this paper, we report the findings of an exploratory study where we investigate the KM practices of eight leading software consultancy companies in India and we suggest a technical and social infrastructure to help enhance KM capability of software development companies in India.